Transseptal Approach Versus Transaortic Approach for Catheter Ablation of Left-Sided Accessory Pathways in Children - Yu, Xia; Dong, Ziyan; Gao, Lu; Lin, Li; Cui, Lang; Shao, Wei; Yu, Wen; Zhen, Zhen; Yuan, Yue (Frontiers in Pediatrics, 2022)
Background Catheter ablation is recommended to eradicate supraventricular tachycardia caused by left-sided accessory pathways (APs) in children. The aim of this study was to compare the safety and efficacy of transseptal approach (TS) and aortic approach (TA) for catheter ablation of left-sided APs in a pediatric cohort. Methods Patients <18 years of age with left-sided APs who had undergone ablation at Beijing Children's Hospital between January 13, 2018 and January 7, 2020 were included and randomly categorized into either TS or TA group. Follow-up for 22 months. In all, 61 patients in TS group and 41 patients in TA group were included in this study. Principal endpoints were success rate, recurrence rate, complications, procedure time, and radiation dose. Results For TS group versus TA group, success rate was observed in 100% versus 97.56% (P=0.402). The procedure time was 27.0 (32.0-23.0) min versus 29.0 (38.0-24.5) min (P=1.107). The rate of success or the procedure time was similar, but for the patients with APs located in left posterior septum (LPS) or left posterior lateral (LPL), the TS group had a shorter procedure time compared with TA group (P<0.01). The radiation dose was 28.0 (20.0-44.0) mGy versus 0 mGy (P<0.001). After successful ablation, no recurrence and complication were observed in either group. Conclusion Both TS and TA for catheter ablation of left-sided APs were shown to be safe and effective in children. Zero radiation and ease of mastery make TA the preferred choice. TS is recommended to be used by properly trained medical professionals, especially for patient with AP localized in the LPL or LPS. However, TS is a good alternative where patients have aortic lesions or when TA fails.